2019
DOI: 10.1371/journal.pone.0221118
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Murine Astrovirus and Myocoptes musculinus in individually ventilated caging systems: Investigations to expose suitable detection methods for routine hygienic monitoring

Abstract: Murine Astrovirus is one of the most prevalent viral agents in laboratory rodent facilities worldwide, but its influence on biomedical research results is poorly examined. Due to possible influence on research results and high seroprevalence rates in mice, it appears useful to include this virus into routine health monitoring programs. In order to establish exhaust air particle PCR as a reliable detection method for Murine Astrovirus infections in mice kept in individually ventilated cages (IVC) and compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Pelage swabs collected from sentinel mice were negative for fur mites by PCR, even though the colony animals had been verified positive. Traditional soiled bedding transfer is known to provide inconsistent detection of fur mites in sentinel animals, 8,[17][18][19]37 and as such our finding is not entirely novel. However, all media samples collected from the soiled bedding of mouse-free experimental cages were positive for fur mites by PCR.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Pelage swabs collected from sentinel mice were negative for fur mites by PCR, even though the colony animals had been verified positive. Traditional soiled bedding transfer is known to provide inconsistent detection of fur mites in sentinel animals, 8,[17][18][19]37 and as such our finding is not entirely novel. However, all media samples collected from the soiled bedding of mouse-free experimental cages were positive for fur mites by PCR.…”
Section: Discussionmentioning
confidence: 69%
“…Several studies have shown that environmental sampling is a viable alternative to traditional sentinel programs. 16,17,23,25,[27][28][29][30][31][32]35,42 The collection and assay of only environmental samples eliminates the need for sentinel animals, leading to a desirable overall reduction in the number of animals used, and the associated reduction in husbandry, labor, and supplies. 22 Although environmental sampling can be done in many ways, the exhaust plenums of individually ventilated caging (IVC) systems have been shown to be a useful sampling location.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, EAD-based monitoring approaches proved to be suitable for a broad variety of infectious agents, such as MNV [ 161 , 167 ], MHV [ 158 ], Murine Astrovirus [ 168 ], Lactate–Dehydrogenase–Elevating–Virus (LDEV) [ 169 ], Rodentibacter sp. [ 153 , 162 ], Helicobacter sp.…”
Section: How To Ensure Qualitymentioning
confidence: 99%
“…[ 160 ], Pneumocystis sp. [ 160 ], fur mites [ 158 , 168 , 170 ], pinworms [ 158 , 164 , 171 ] and enteric protozoa [ 158 , 159 , 160 ]. However, infections with murine Parvoviruses and Klebsiella oxytoca could not be confirmed by this method so far [ 158 , 159 ], and in the case of Staphylococcus aureus there exist contrasting results [ 159 , 160 ].…”
Section: How To Ensure Qualitymentioning
confidence: 99%